The Effectiveness of Contextual Teaching and Learning with Multimedia to Increase Student’s Achievement on Hydrocarbon Topic - Lubis, Ervi Luthfi Sheila Wanni; Rahmania, Sri; Siregar, Anisyah (LAVOISIER: Chemistry Education Journal, 2022)
This research have objective to increase student achievement taught with contextual teaching and learning is better than student achievement taught with direct instruction in hydrocarbon topic, to growth characteric of comunicative in learning with contextual teaching and learning is better than learning with direct intruction. to know the effectivity of student achievement taught by contextual teaching and learning compare than student’s achievement taught by direct instruction. Population of this research are SMAN 16 Medan, SMAN 1 Sunggal and MAS PAB 2. Sample on this research are X grades. The study followed by pretest as the preliminary evaluation. then give treated Contextual Teaching Learning in experimental class, Direct Instruction in control class. And give postest as evaluation test. In pretest, average of pretest in experiment class is 36.11 and in control class is 39.11. In postest, experiment class is 82 and control class is 73.11. The comparison based on gain of pretest and postest data of experiment and control is 71 and 55, the effectivity is 22.53. So, student’s  Achivement in class that teaching with Contextual Teaching Learning is significant better than control class that teaching with Direct Instruction. the percentage of students character in experiment class is 67.80 and control class is 58.20